Deterministic patterned growth of high-mobility large-crystal graphene: a path towards wafer scale integration. (19th January 2017) - Miseikis, Vaidotas; Bianco, Federica; David, Jérémy; Gemmi, Mauro; Pellegrini, Vittorio; Romagnoli, Marco; Coletti, Camilla
Abstract: We demonstrate rapid deterministic (seeded) growth of large single-crystals of graphene by chemical vapour deposition (CVD) utilising pre-patterned copper substrates with chromium nucleation sites. Arrays of graphene single-crystals as large as several hundred microns are grown with a periodicity of up to 1 mm. The graphene is transferred to target substrates using aligned and contamination- free semi-dry transfer. The high quality of the synthesised graphene is confirmed by Raman spectroscopy and transport measurements, demonstrating room-temperature carrier mobility of 21 000 cm 2 V −1 s −1 when transferred on top of hexagonal boron nitride. By tailoring the nucleation of large single-crystals according to the desired device geometry, it will be possible to produce complex device architectures based on single-crystal graphene, thus paving the way to the adoption of CVD graphene in wafer-scale fabrication.